Penyuluhan Hukum Tentang Perlindungan Anak dan Pencegahan Kekerasan di Lingkungan Sekolah SMPN 1 Parangloe Kabupaten Gowa Sulawesi Selatan - Andi Muhammad Fiqry Haykal; Husniar Darsis (Lembaga Pengembangan Kinerja Dosen, 2025)
Violence against children in the school environment is a serious problem that requires special attention. This legal counseling activity aims to increase understanding of child protection and violence prevention, especially at SMPN 1 Parangloe, Gowa Regency, South Sulawesi. Through counseling methods, interactive discussions, and documentation, the research team successfully involved 50 students, 3 teachers, and 7 parents in the activity held on February 24, 2025. The results showed a significant increase in participants' awareness of children's rights and steps to prevent violence. Students became more active in participating in discussions and more courageous in reporting cases of violence they experienced or witnessed. However, challenges such as concerns about social stigma are still barriers that need to be overcome. This activity emphasized the importance of collaboration between schools, parents and communities to create a safe and supportive environment for children's development. Thus, this counseling not only provides knowledge but also builds children's confidence in dealing with potential violence at school.